Sistem Pendukung Keputusan Penilaian Karyawan PT. Season Miracle Indonesia Menggunakan Metode MAUT - Nicholas Robert Renaldi Lau (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2026)
PT. Season Miracle Indonesia is a company engaged in the trading of various goods such as office stationery, food, and clothing, as well as providing photocopying, printing, and photo printing services. In its operational activities, the company conducts employee evaluations to determine the best-performing employee. However, the current evaluation process is still carried out in a simple manner, which may lead to subjectivity and requires a considerable amount of time. This study aims to develop a Decision Support System (DSS) that can assist the employee evaluation process and implement the Multi-Attribute Utility Theory (MAUT) method in determining the best employee at PT. Season Miracle Indonesia. The system was developed using PHP programming language with Visual Studio Code, while the database was designed using MySQL and XAMPP. The system development methodology employed in this research was the Iterative method. The results indicate that the developed system is capable of managing the employee evaluation process more efficiently, generating employee rankings objectively based on predetermined criteria, and assisting management in making decisions more quickly, accurately, and accountably.